Seasonal Succession of Zooplankton of Three Distinct Aquaculture Ponds in Chattogram, Bangladesh (Journal of the Bangladesh Agricultural University, 2024)
Zooplankton is crucial dietary sources for omnivorous fishes and an essential component in freshwater food webs. A six-month investigation carried out from February to July 2023, encompassing three separate seasons, to examine the abundance and variety of zooplankton in connection to physico-chemical parameters in three different waterbodies: intensive, semi-intensive and extensive ponds at Chittagong University campus. Two ponds were chosen for each of the waterbodies that were classified. Monthly fluctuations of some physico-chemical parameters were noted. Most of the ponds were found to be alkaline and TDS, EC, and the variations of air and water temperature were also examined. Remarkable correlations observed between zooplankton and several physico-chemical parameters, either directly or indirectly. Zooplankton in Intensive ponds showed positive significant relationship with TDS (r=0.78, P< 0.1), EC (r=0.81, P< 0.05) and pH (r=0.34, P